Dioxygenase-encoding AtDAO1 gene controls IAA oxidation and homeostasis in Arabidopsis - Porco, Silvana; Pěnčík, Aleš; Rashed, Afaf; Voss, Ute; Casanova-Sáez, Rubén; Bishopp, Antony; Golebiowska, Agata; Bhosale, Rahul; Swarup, Ranjan; Swarup, Kamal; Peňáková, Pavlína; Novak, Ondrej; et al. (National Academy of Sciences, 2016)
Auxin represents a key signal in plants, regulating almost every aspect of their growth and development. Major breakthroughs have been made dissecting the molecular basis of auxin transport, perception, and response. In contrast, how plants control the metabolism and homeostasis of the major form of auxin in plants, indole-3-acetic acid (IAA), remains unclear. In this paper, we initially describe the function of the Arabidopsis thaliana gene DIOXYGENASE FOR AUXIN OXIDATION 1 (AtDAO1). Transcriptional and translational reporter lines revealed that AtDAO1 encodes a highly root expressed, cytoplasmically localized IAA oxidase. Stable isotope-labeled IAA feeding studies of loss and gain of function AtDAO1 lines showed that this oxidase represents the major regulator of auxin degradation to 2-oxoindole 3-acetic acid (oxIAA) in Arabidopsis. Surprisingly, AtDAO1 loss and gain of function lines exhibited relatively subtle auxin-related phenotypes, such as altered root hair length. Metabolite profiling of mutant lines revealed that disrupting AtDAO1 regulation resulted in major changes in steady-state levels of oxIAA and IAA conjugates but not IAA. Hence, IAA conjugation and catabolism seem to regulate auxin levels in Arabidopsis in a highly redundant manner. We observed that transcripts of AtDOA1 IAA oxidase and GH3 IAA-conjugating enzymes are auxin-inducible, providing a molecular basis for their observed functional redundancy. We conclude that the AtDAO1 gene plays a key role regulating auxin homeostasis in Arabidopsis, acting in concert with GH3 genes, to maintain auxin concentration at optimal levels for plant growth and development.